The challenges in the reading of legal cases: students’ perspective - Ariffin, Adlina (2013)
The ability to read legal cases is one of the most essential skills for law students to be successful in their discipline. It is particularly fundamental since case law is one of the main sources of law. Christensen (2006) in her research entitled "Legal Reading and Success in Law School: An Empirical Study" shows that students who are able to read judicial opinions effectively and efficiently are more successful in their studies. However, the most common assumption is that students would have possessed this skill when they enroll in a law school. This attitudinal fallacy is referred to as “skills deployment assumption” (Stratman, 1990). Thus, this paper describes a research which attempted to investigate the quintessential elements in the reading of legal cases among law students in a Malaysian public university. Specifically, it aimed to develop some understanding on the reading of this rhetorical genre and simultaneously uncover the problems related to the learning process. This study which adopted a case study design obtained the data through interview sessions with twelve law students. The major finding of this research showed that despite the training given to the students, they still faced a lot of problems in acquiring this crucial skill. These challenges emanated from three main aspects i.e. language, time management and nature of legal cases.